Numerical Study and Comparison of Various Types of Insulation Systems in Terms of Controlling Heat in Cryogenic Tanks - Sobhan Safavi Manesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to numerically compare the thermal performance of various insulation systems and also to maximally reduce the ambient heat transferred to the cryogenic fluid stored in a tank. For this, we use such techniques as vacuum insulation, cryogenic cold shell around the main tank, multilayer insulation, two-sided insulation around the external tank, polyurethane insulation and anti-radiation coatings. The findings suggest that the thermal emissivity and vacuum pressure as well as the vacuum thickness are critical parameters affecting the inlet thermal emission to the main tank. The use of a cryogenic cold shell in a vacuum space is shown to cause a significant drop in the inlet thermal emission to the tank. Considering the separator material inside the various layers of different thicknesses, the multi-layer insulation is also modeled. In this situation, a layer density of 26 cm-1 has been regarded as the best layer density. Finally, while modeling several examples of composite insulation, the intra-tank evaporation rate for each insulation and the feasibility of using the mentioned insulation in Iran are provided.